Procesos didácticos de la lectura y la comprensión lectora en los niños de la institución educativa inicial Nº 728, Caballo Cocha 2024 - Torres Garcia, Flor Lila (2025)
The purpose of this research study is to analyze the relationship between the didactic processes of reading and the levels of reading comprehension in the children of the Initial Educational Institution No. 728 Caballo Cocha in the year 2024. This study, with a quantitative approach, is classified as relational research. The design adopted is non-experimental, correlational, and transactional. The study population is made up of all the boys and girls enrolled in the Initial Educational Institution No. 728 Caballo Cocha during 2024, totaling 118 children. For data collection, the observation technique has been used, employing an observation guide as the instrumentó. Regarding the validity of the instrumentó, it will be evaluated by a team of experts with extensive experience in the field, ensuring that the categories and behaviors identified are relevant and appropriate. The results obtained, with a correlation coefficient of 0.754 and bilateral significance of 0.05, demonstrate that the relationship between the variables is statistically significant. Consequently, the null hypothesis is rejected, and the general hypothesis is confirmed. This allows for the conclusion that there is a significant relationship between learning projects and the holistic development of children in the Initial Educational Institution No. 728 Caballo Cocha.